Anestezjologia i intensywna terapiaPropofol anaesthesia for elective electrical cardioversion among patients in various age groups - Siedy, Janusz; Knapik, Piotr; Saucha, Wojciech; Gross, Maria (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Electrical cardioversion using propofol as a sole hypnotic agent is a frequent, standard procedure. The aim of this study was to compare the course of anaesthesia with propofol for this procedure among patients in various age groups. Material and Methods: 50 patients, aged 32 to 87 years, underwent elective electrical cardioversion for various atrial arrhythmias. Patients were stratified into two age groups – group I (Ł65 years, n=31) and group II (>65 years, n=19). Patients were given propofol (bolus 1 mg kg–1, followed by increments containing 20% of the initial dose) as a sole agent. Results: Haemodynamic parameters were similar in both groups. Anaesthesia and awakening times were not significantly different between groups. Anaesthesia time was 10.7±3.1 min. for group I and 10.6±2.9 min. for group II, while awakening time was 4.8±2.5 min. for group I and 4.7±1.8 min. for group II. Mean use of propofol, number of electrical impulses and total electrical energy delivered to regain sinus rhythm were significantly higher in younger patients. Propofol dose required to provide anaesthesia was 1.81±0.51 mg/kg in group I and 1.49±0.46 mg/kg in group II (p=0.026). Overall, electrical cardioversion was successful in 77% of patients in the younger group and in 89% of patients in the older group (p=NS). Maximal motor response to consecutive electrical impulses was less pronounced in older patients. Frequency of side-effects was not statistically different between groups apart from more incidents of apnoea among older patients (0 vs. 15.8%). Conclusion: Electrical cardioversion with titrated administration of propofol as a sole agent is safe for patients in various age groups. Apnoea and mild desaturation are more frequent in older patients, whereas younger patients may present more pronounced motor response and require a higher dose of the hypnotic agent.